Incidencia de la serie televisiva tres familias en el comportamiento de los adolescentes de 12 a 16 años en la cooperativa Lomas de la Florida de Guayaquil - Cercado Santillán, Diana Tairy (2016)
Ecuadorian television are innovating its contents and today you can see a lot of programs, series, soap operas with an understandable content for all social strata and present realities with which the audience can identify. All this really does not mean that programs that offer TV channels are healthy for the public that consumes them, because Ecuadorian society needs to improve its analytical capacity regarding the content presented and likewise should learn to discriminate programs that they are beneficial and which may affect the behavior of people……